Lead Fracture as a Cause of Pacemaker Failure: A Case Report - Majumder, Abdullah Al Shafi; Chowdhury, Abdul Wadud; Islam, AEM Mazharul; Muttalib, Md Abdul; Alam, Mahinoor Mortuja (University Heart Journal, 2008)
(University Heart Journal 2007; 3 : 87-89)